Insecticide toxicity to Hyalella curvispina in runoff and stream water within a soybean farm (Buenos Aires, Argentina) - Mugni, Hernan Diego (2011)
Toxicity to the locally dominant amphipod Hyalella curvispina was assessed in a first-order stream running through a cultivated farm. Cypermethrin, chlorpyrifos, endosulfan and glyphosate were sprayed through out the studied period. Toxicity was assayed under controlled laboratory conditions with runoff and stream water samples taken from the field under steady state and flood conditions. Ephemeral toxicity pulses were observed as a consequence of arm pesticide applications. After Pesticide application, runoff water showed 100% mortality to H. curvispina for 1month, but no mortality thereafter.Toxicity persistence was shortest in stream water, intermediate instream sediments and longest in soil samples. Runoff had a more important toxicity effect than the exposure to direct aerial fumigation. The regional environmental features determining fast toxicity dissipation are discussed.